Resignified local histories in the training process of teachers (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2019)
This article shows the creation, development and results of an educational research line within the Master in History of the Technological University of Pereira. The successes and difficulties that arose from the conception of the same are underlined, exploring the path of urban, local and neighborhood history as a scenario of didactic reflection in social science classes, and as a strategy to address the problem of the formation of teaching staff at the post graduate level and its multiple impacts at the regional level. The experience developed showed that the approach was useful and relevant according to the interests of the educational institutions and the participating teachers. It has been tried that the deepening in the local histories realizes a critical distancing of the myths of the colonization, inviting to generate a greater inclusion of new actors and stories in the construction of the regional history. Similarly, a renewal speech has been promoted in the exercise of history.
Keywords: teaching of history; the historian's office; local history; neighborhood history; historical sources